Purification: A Serious Game Of Environmental Issues - Leong, Pi Yee (2023)
Over the past few decades, new environmental problems have emerged, and a series of environmental problems have devastated our entire planet. Apart from developing the economy and improving the quality of life, people do not care about the importance of environmental protection. Although the government and environmental groups are promoting the importance of environmental protection through posters, advertisements and lectures, there is still a lack of action to protect the environment. Especially young people these days, they will find these activities boring. So, this project is to develop a serious game called "Purification", which focuses on raising awareness of environmental issues among the youth age group. In this project, the environmental issues can be categorized into five categories: air pollution, water pollution, deforestation, climate change, and waste management. The objective of this project is to study the game mechanics of the developed 2D platform serious game, to design and develop a 2D platform serious game with a combined storyline and gameplay and evaluate the functionality of the developed 2D platform serious game. This project is developed by using the methodology of Rapid Application Development (RAD), which is intended for individual developers who need to complete projects within a short period of time. The game is developed using the Unity engine, designed using Clip Studio Paint and Photoshop, and uses royalty-free audio from the internet. The final product is deployed on PC platforms and on Itch.io, a web page where people can upload or play games. The expected outcome of this project is that users can play the game and achieve the stated project goals.